2022
DOI: 10.51620/0869-2084-2022-67-1-24-30
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of erythrocyte parameters of general blood analysis in patients with SARS-CoV-2 -associated pneumonia

Abstract: The study of the features and dynamics of the erythrocyte parameters of general blood analysis in patients with cardiovascular diseases who underwent SARS-CoV-2 associated pneumonia is of great practical importance. That was a prospective study. The study included 106 patients with SARS-CoV-2-associated pneumonia. All patients were divided into 2 groups. The first group included 51 patients without CVD, the second group included 55 patients with CVD .Patients in both groups underwent laboratory examination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“… 6 , 11 Patients with or without CVD Covid-19 significantly increased MCV and decreased RDW three months after discharge. 35 Similarly, our study showed a rise in MVC and a reduction in RDW after the discharge in both severe and non-severe cases. Notably, RDW was a significant difference between severe and non-severe patients.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“… 6 , 11 Patients with or without CVD Covid-19 significantly increased MCV and decreased RDW three months after discharge. 35 Similarly, our study showed a rise in MVC and a reduction in RDW after the discharge in both severe and non-severe cases. Notably, RDW was a significant difference between severe and non-severe patients.…”
Section: Discussionsupporting
confidence: 77%
“…The study showed that when the coefficient of variation of RDW was greater than 13.6, the likelihood of lung tissue injury increased by 9.3 times, and it was a lung volume marker for COVID-19 severity. 35 Studies have proved that increased RDW is common in human disorders, including cardiovascular disease, 36 venous thromboembolism, 37 cancer, 38 diabetes, 39 community-acquired pneumonia, chronic obstructive pulmonary disease, 37 liver, 40 and kidney failure, 41 and so on. Increased RDW reflects a severe dysregulation of erythrocyte homeostasis, including impaired erythropoiesis and abnormal erythrocyte survival.…”
Section: Discussionmentioning
confidence: 99%
“…In their trial on patients with and without cardiovascular disease who suffered from SARS-CoV-2-related pneumonia, Petelina et al prospectively studied the blood samples of both cohorts during their hospitalization as well as three months after their discharge [14]. They noted a significant elevation in hematocrit (HCT), mean corpuscular volume (MCV), and MCH (mean corpuscular hemoglobin) in both patient cohorts, and a decrease in mean corpuscular hemoglobin concentration (MCHC) and RDW-CV in both cohorts (p<0.001 for all parameters).…”
Section: Discussionmentioning
confidence: 99%